Density And Capacity Of Bali Cattle Seed Source Area In Buke District, South Konawe Regency - Abadi, Musram; Nafiu, La Ode; Saili, Takdir; Gerhana, Gerhana; Yunus, Lukman; Dedu, La Ode Arfan; Rizal, Abdul (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This study is conducted to analyze livestock density (area density, farming density, economic density) and the capacity to increase the ruminant population (CIRP) in Buke District, South Konawe Regency. The research location is determined through purposive sampling in Buke Subdistrict, South Konawe Regency, with all Bali cattle breeders in the area being involved as respondents, totaling 734 breeders. The data are analyzed using livestock density analysis (area density, farming density, economic density) (Ashari et al., 1995), a combination of livestock density (Rahaeni, 2014), and the capacity to increase the ruminant population (CIRP) (Fariani, 2008). Based on the study results, it is shown that the density of Bali cattle in Buke Subdistrict is at an economic density of 97,11 AU/1,000 people, a farm density of 0,16 AU/ha, and an area density of 7,75 AU/km². The combination of livestock density is categorized as a dispersal and development area, while the capacity based on natural resources is recorded at 4.951 AU. Therefore, it is concluded that the density of Bali cattle in Buke Subdistrict varies depending on the indicators used. In economic terms, livestock density is classified as medium, whereas in terms of land area and regional distribution, it is considered sparse. Overall, the area is categorized as a dispersal and development region, with the capacity to accommodate Bali cattle based on available natural resources.